Competitive Advantages of Serbian Industry Sectors - Dobromirov, Dusan; Radisic, Mladen; Celic, Djordje; Bojovic, Viktorija (International Journal of Industrial Engineering and Management, 2012)
This paper presents an overview of industry sectors in the Republic of Serbia, with their recent export and import data comparison. Being the country that is proceeding with the EU integration process, Republic of Serbia has to undertake major society and economic changes. In light of those changes, the country has to define its most important industries and to enforce progress within those flagship sectors. In our research, we will present a methodology that examines an industry’s competitive advantage. According to our findings, we propose possible strategic alternatives on the national level in Republic of Serbia, which can be used by Serbian economic policy makers. Article history: Received (17 December 2011); Revised (19 January 2012); Accepted (10 February 2012)